Assessment of Floristic, Microbial Composition and Growth of Sphenostylis stenocarpa (Hochst Ex A. Rich) in Soil from Two Dumpsites in Benin City, Nigeria - G.C. Mgbeze; J.O. Osazee (Journal of Basic & Applied Sciences, 2014)
Survey of dumpsite plant composition, assessment of rhizosphere microorganisms and growth performance of Sphenostylis stenocarpa grown on two dumpsite (CAPITOL and NITEL ROAD) soils in Benin City was investigated. Control treatment was top soil. A total of 9 and 30 flora were observed at the CAPITOL and NITEL ROAD dumpsites respectively. Analysis of the rhizosphere soils of the plants grown in dumpsite soils at different amendments showed a total heterotrophic bacterial count ranging from 1.57 x 104 to 4.18 x 104cfu/g and a total heterotrophic fungal count in the various rhizosphere soils ranged from 5.05 x 103 to 1.68 x 104cfu/g. The bacterial isolates from the rhizosphere soil samples were Arthrobacter sp., Bacillus sp, Pseudomonas sp., Escherichia coli, Enterobacter sp., Klebsiella sp., Micrococcus sp. and Staphylococcus sp. The fungal isolates were Aspergillus sp, Mucor sp, Fusarium sp, Penicillium sp, Trichoderma sp. and Saccharomyces sp. Bacillus sp., Pseudomonas sp., Penicillium sp. and Aspergillus sp. Aspergillus sp. 100 % (present in all dumpsite soils analyzed) had the highest frequency of occurrence amongst the isolates.Percentage seedling emergence was significantly reduced from 86.67± 13.33 % - 100.00 ± 0.00 % in control (top) soil to 60.00 ± 0.00 % to 93.33 ± 6.67 % in CAPITOL dumpsite soil. Shoot height at 6 weeks after planting (WAP) was significantly (p < 0.05) increased from 78.33± 18.53 cm in the control soil through 131.50 ± 18.79 cm in the CAPITOL dumpsite soil to 186.33 ± 13.68 cm in NITEL road dumpsite soil, all without amendment. Number of leaves at 6 WAP increased on addition of FYM in both soil types. Chlorophyll content was not significantly different (p > 0.05) from control plants. Leaf area in both dumpsite soils was found to be significantly different (p < 0.05) from the control soil but leaf area increased on addition and increase in amendment in both soil types. In all parameters observed, it was noted that the control treatment did better than the plants grown in the dumpsite soils with increased amendment..